The Theory of Credibility and the Reputation-Bias of Policy. - Forder, J (Taylor and Francis, 2001)
The theory of policy credibility has been influential in both the design of monetary policymaking institutions and in the implementation of policy. In particular, the idea that 'reputation' is important has been widely accepted. However, careful attention to the assumptions and implications of the theory reveals many sources of doubt as to its empirical value. First, the theory is implausible and, even if taken seriously, does not point to many of the conclusions frequently supposed to be based on it. Second, evidence suggests the theory is false. Third, even policymakers who profess themselves concerned about the maintenance of credibility do not behave consistently in the way the theory says they should. Although many policy proposals ostensibly based on the theory of credibility therefore seem to lack persuasive support, the idea of credibility still poses a danger to effective policymaking since it creates motives for excessively contractionary policy. Although it is frequently asserted that monetary policy can have no long-term effects on economic performance, the idea that a loss of 'reputation' will have lasting detrimental effects appears to motivate much policy. In the absence of convincing arguments that reputation - in its technical sense - is important, this would seem to be undesirable and probably dangerous.